EFEKTIVITAS PENGGUNAAN MEDIA WORDWALL TERHADAP KEMAMPUAN BERFIKIR KRITIS PESERTA DIDIK PADA MATA PEMBELAJARAN MATEMATIKA DI SD MUHAMMADIYAH AMBARBINANGUN BANTUL - Icsan Angrian; Urip Muhayat Wiji Wahyudi (STKIP Subang, 2025)
This study aims to determine the effectiveness of using wordwalls in improving critical thinking in fifth-grade students in mathematics, particularly in fractions. As a control group, Class VA did not get any media, whereas Class VB was the experimental group that did receive media. The data was gathered by testing and careful observation. The next step in the data analysis process was to administer prerequisite exams and use an Independent Sample T-test to evaluate hypotheses. The average scores significantly increased from 51.08 before therapy to 87.05 after treatment, thanks to the application of wordwalls. Meanwhile, the control class also experienced an increase from 46.88 to 79.16. The t-test yielded a significant value of 0.001.